Sumber Makna Hidup Santri Mengabdi di Pondok Pesantren - Erny Fitroh Nabila Muwafiqi; Yulia Sholichatun; Iin Tri Rahayu (Fakultas Dakwah UIN KHAS Jember, 2025)
Globally, santri are people who are studying Islamic religion at Islamic boarding school institutions. If classified, santri are divided into two types, namely mukim santri and kalong santri. However, in this research, there is one more classification related to santri, namely santri who devote themselves to caregivers either for the benefit of the santri or caregiver. The research method used is a qualitative method with a grounded theory approach. The data collection process in this study was carried out by interviewing research subjects. The results of this research are that the meaningfulness of life of serving students can be seen from: 1) Social pressure, 2) Self-formation, 3) Grounding techniques, 4) Spirituality.